Against the communitarian republic - KUKATHAS, Chandran (Institutional Knowledge at Singapore Management University, 1996)
Communitarianism has risen to prominence in recent debates in political philosophy largely on the strength of its criticisms of liberalism. Among its more important criticisms is the charge that liberal political thinking does not properly appreciate the value of community. At a deeper level, communitarian ism asserts that liberalism is infected by confusions about the nature of community, thinking?mistakenly?that it is no more than an associa tion of separate, isolated, 'atomistic' individuals. Communitarians thus advance not only certain claims about value but also other claims about how the human world should be understood.